ANALISIS PENGARUH LITERASI KEUANGAN DAN LITERASI DIGITAL TERHADAP PEMANFAATAN APLIKASI AKUNTANSI PADA UMKM DI KOTA TEGAL - Aryanto Aryanto; Fitri Amaliyah Fitri Amaliyah; Ida Farida (Perwira Journal of Economics & Business, 2026)
MSMEs play a crucial role in the national economy, but the utilization of accounting technology in financial management is still not optimal. One of the main factors hindering the adoption of accounting applications is the low financial and digital literacy among MSME players. This study aims to explore the influence of financial and digital literacy on the use of accounting applications by MSMEs in Tegal City. Using a quantitative approach, this study applied the Structural Equation Modeling method based on Partial Least Squares (PLS-SEM) with the help of SmartPLS 3 software. Data were collected through questionnaires distributed to 65 MSME respondents using simple random sampling technique. The results indicate that both financial and digital literacy have a positive and significant influence on the utilization of accounting applications, with digital literacy showing a more dominant influence. This research model is able to explain 63.1% of the variation in the utilization of these applications. The findings provide insights for the development of strategies to improve financial and digital literacy for MSMEs, in order to accelerate their digital transformation. In its implementation, the government and app developers are expected to collaborate to provide integrated training that encourages wider and more effective adoption of accounting technology.